Social bioarchaeology (Chichester, West Sussex)
xx, 449 sayfa
Keywords: “Social bioarchaeology introduces the exciting and growing biosocial approach in archaeology that challenges the traditional methods of analyzing and interpreting human skeletal remains. Agarwal, Glencross, and the experts assembled in this volume outline the essential components of this research, focusing on the dynamic interactions between humans and their larger social, cultural, and physical environments, and how these analyses increase our understanding of human adaptation. The authors draw upon studies from the Americas, Europe, and the Middle East examining the central themes, theoretical issues, and methodological innovations in the field. Each chapter offers significant new research that integrates elements from biological, behavioural, ecological and social research. This new volume will be a valuable resource for archaeologists, biological anthropologists, paleopathologists, and all researchers with an interest in understanding our social and biological adaptations in a constantly changing global environment.“ --